PENGARUH STRATEGI DIGITAL MARKETING TERHADAP BRAND AWARENESS DAN LOYALITAS PELANGGAN STARTUP E-COMMERCE - Ali, Ali Marwan Hanan; Puteri Andini, Dea; Galank Oktavan, Doa (PT. ABIG RIZKY PUBLISHER, 2026)
This study aims to analyze the effect of digital marketing strategies on brand awareness and customer loyalty in e-commerce startups, specifically Shopee and Tokopedia in Indonesia. Digital transformation has changed consumer shopping behavior, making brand strength and emotional closeness key to business sustainability. The method used is a quantitative associative approach with a sample of 100 active users selected through purposive sampling. Primary data were collected through structured questionnaires and analyzed using multiple linear regression with the help of SPSS software. The results show that digital marketing strategies have a positive and significant effect, both partially and simultaneously, on brand awareness and customer loyalty. The Adjusted R Square value of 0.712 indicates that digital marketing strategies are able to explain 71.2% of the variation in the two dependent variables, while the remainder is influenced by factors outside the model. These findings confirm that instruments such as social media, digital advertising, SEO, and application-based promotions play a dominant role in increasing brand recognition and building long-term consumer commitment amid intense digital market competition.